Formation of Professional Orientation of High School Students to Medical Profession by Using ICT Tools - Molodozhnikova, Natalia Mikhailovna; Biryukova, Natalia Viktorovna; Galustyan, Olga Vladimirovna; Lazareva, Julia Borisovna; Stroiteleva, Natalia Nikolaevna (International Journal of Emerging Technologies in Learning (iJET), 2020)
The article is devoted to the formation of professional orientation of students to medical profession by using ICT tools. The article deals with the problem of professional orientation and formation of interest to the medical profession at schools with biological and medical classes. The use of ICT tools contributes to the integration of school subjects into current knowledge which are necessary for the future effective work of medical specialists. Application of ICT increases the effectiveness of professional orientational classes, improves students’ awareness of their future profession, implements to the professional choice based on the awareness and understanding of students of their professional preferences and aptitudes. This technique makes it possible to form not only an adequate motivation to the medical profession, but also interest in disciplines connected with future profession.